A Palladium-Catalyzed Oxa-(4+4)-Cycloaddition Strategy Towards Oxazocine Scaffolds - Scuiller, Anaïs; Liu, Xueyang; Cordier, Marie; Garrec, Julian; Archambeau, Alexis (Synlett, 2021)
A Pd-catalyzed oxa-(4+4)-cycloaddition between 1-azadienes and (2-hydroxymethyl)allyl carbonates is described. Aurone-derived azadienes furnished polycyclic 1,5-oxazocines in good yields. Interestingly, linear azadienes have also been involved and yielded monocyclic heterocycles with complete regioselectivity. DFT calculations were carried out to gain insight on this observation.
Keywords: cycloaddition; catalysis; heterocycles; medium-sized rings; oxazocines; azadienes